Urgensi Ilmu Kedokteran Islam dengan Hukum Islam (Studi Identifikasi Deoxrybo Nucleic Acid (DNA) terhadap Sepersusuan) - Manzil, Li’izza Diana (Fakultas Syariah IAIN Purwokerto, 2018)
One sign of the rapidly growing world of medical science is its success in making one discovery about Deoxrybo Nucleid Acid (DNA). Islam does not prohibit the practice of DNA identification because it can be used in determining the legal status of relative relationships and related marital prohibitions among families because of the similarity of DNA genes between parents and their children. In Islam marriage prohibition can also occur between brothers and sisters. DNA identification can be done between siblings as a result of the presence of gene elements in breast milk. In addition, breast milk can also develop bone and grow meat if breastfeeding at least five times suction. But the results of DNA tests conducted between siblings cannot be more accurate if done to find relationships of parents and children. From this it clearly proves that Islamic medicine has an urgent value to Islamic law. This can be seen from one of its axiology in determining the status of brotherhood.